Examination of Efficient Operation Method of ATES System by Comparison Operation with WTES System of Existent Heat Storage System - Jewon Oh; Daisuke Sumiyoshi; Masatoshi Nishioka; Hyunbae Kim (Applied Sciences, 2021)
Aquifer thermal energy storage (ATES) system is widely used mainly in Europe and USA. In this paper, we examined the efficient operation method of ATES by comparing it with the water thermal energy storage (WTES) system of an existent thermal energy storage (TES) system using simulation. This study uses three aquifers: pumping wells, thermal storage wells, and reducing wells. The initial temperature is 19.1 °C groundwater from the surrounding area. ATES systems use the same operating methods as WTES systems to reduce heat storage efficiency and increase energy consumption. The operation that combines the ATES system with the pre-cooling/pre-heating coil can be used for air conditioning operation even if the heat storage diffuses or the pumping temperature changes. The aquifer heat storage system was used for the pre-cooling/pre-heating coil, and the cooling power consumption was reduced by 20%. The heating operation could not maintain heat for a long time due to the influence of groundwater flowing in from the surroundings. Therefore, it is recommended to use the stored heat as soon as possible. When energy saving is important by introducing a pre-cooling/pre-heating coil, the operation is performed by storing heat at a low temperature close to geothermal heat and also using groundwater heat. In addition, if the reduction of peak power in the daytime is important, it is appropriate to operate so that the heat stored in the pre-cooling/pre-heating coil is used up as much as possible. As a result, it was found that it is effective to operate the ATES system in combination with a pre-cooling/pre-heating coil. In cooling operation, ATES-C1-7 was the lowest at coefficient of performance (COP) 2.4 and ATES-C2-14 was the highest at COP 3.7. In heating operation, ATES-H1-45 was the lowest at COP1.2, and in other cases, it was about the same at COP2.4-2.8. In terms of energy efficiency, the heating operation ATES-H1-45 had a low energy efficiency of 4.1 for energy efficiency ratio (EER) and 3.9 for seasonal energy efficiency ratio (SEER). In other cases, the energy efficiency was 8.2–12.4 for EER and 8.7–15.3 for SEER.